Economic Growth and Productivity in the United States, Canada, United Kingdom, Germany and Japan in the Post-War Period - Domar, Evsey D.; Eddie, Scott M.; Herrick, Bruce H.; Hohenberg, Paul M.; Intriligator, Michael D.; Miyamoto, Ichizo (The Review of Economics and Statistics, 1964)
Evsey D. Domar, Scott M. Eddie, Bruce H. Herrick, Paul M. Hohenberg, Michael D. Intriligator, Ichizo Miyamoto, Economic Growth and Productivity in the United States, Canada, United Kingdom, Germany and Japan in the Post-War Period, The Review of Economics and Statistics, Vol. 46, No. 1 (Feb., 1964), pp. 33-40